Administrative Dispute Reform : New Attempt – Old Problems - Radošević, Ratko S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
A decade ago, Serbia has carried out the reform of judicial control of public administration – by establishing the new Administrative Court. The expected results, however, have not been achieved and the problems that caused the reform have not been resolved. Therefore, a decade later, a new reform is in sight. The planned changes include establishing more administrative courts and introducing a two-instance administrative dispute. The aim of this paper is to discuss these changes, but in a slightly different way. Instead of their uncritical acceptance and justification by European legal standards, they are analysed having in mind the legal nature of the administrative dispute. Successful administrative dispute reform cannot be achieved if European legal standards are blindly accepted and copied literally from classical court proceedings. Only the legal nature of the administrative dispute and the features that make it special and different from the usual court disputes can lead us to a successful implementation of the changes.